Iron-Dextran Enhancement of 67Ga-Concentration in Abscess Relative to Normal Tissue - Larson, S. M.; Mahler, D.; Allen, D.R. (Nuklearmedizin - NuclearMedicine, 1978)
Iron-dextran (Imferon®) significantly increases the concentration of 67Ga in abscess relative to muscle, when given intravenously to abscess bearing rabbits 24 hr after intravenous, carrier-free 67Ga-citrate. This increase is achieved by accelerating the clearance of 67Ga from the blood.